وقف النقود ودوره في تطوير البحث العلمي جامعة الملك عبد العزيز آل سعود أنموذجا - وصيف خالد, إبراهيم (University of Eloued جامعة الوادي, 2021)
تبحث الأطروحة موضوع وقف النقود باعتباره آلية فعالة لتجميع الأموال وصرفها لتطوير الأبحاث العلمية، معتمدة في ذلك على ميزة المرونة التي يتمتع بها نظام الوقف وقابلية أحكامه للاجتهاد والتطوير. تعرضت في القسم النظري إلى الأحكام العامة للوقف وركّزت على وقف النقود تبيانا لأحكامه ومميزاته، ثم حاولت الربط بين البحث العلمي ومستلزمات تطويره وبالأخص مستلزم التمويل وفق معادلة ثلاثية محصلتها أن التطوير يستلزم تفكيرا استراتيجيا وتمويلا، مع مراعاة اعتماد التمويل على التخطيط الاستراتيجي. وفي الجانب التطبيقي اختارت الدراسة الوقف العلمي بجامعة الملك عبد العزيز ال سعود، باعتماد البيانات المنشورة على الموقع الضخم لجامعة الملك عبد العزيز، واعتمدت أسلوب المقارنة بين نتائج الوقف العلمي على مدار عشر سنوات مقسّمة على ثلاث مراحل. خلصت الدراسة إلى إمكانية إسهام وقف النقود في عمليات التطوير بجميع مستوياتها المثبتة في المعادلة التطويرية، وأنه بالإمكان اعتماد النموذج التطويري المعتمد في الوقف العلمي لاعتماده على أحد النظريات كالكايزن وبطاقات الأداء المتوازن في تنظيم المؤسسات. The thesis examines the issue of Cash waqf (Endowment) as an effective mechanism for raising funds and spending them to develop scientific research, relying on this on the advantage of the flexibility enjoyed by the endowment system and the ability of its provisions for diligence and development. In the theoretical section, I was exposed to the general provisions of the endowment and focused on Cash waqf (Endowment) in explanation of its provisions and advantages, then I tried to link scientific research with the requirements of its development, especially the necessity of financing according to a three-way equation whose conclusion that development requires strategic thinking and financing, taking into account the dependence of financing on strategic planning. On the practical side, the study chose the scientific endowment at King Abdulaziz University, by adopting the data published on the huge site of King Abdulaziz University, and the method of comparing the results of the scientific endowment over a period of ten years divided in three phases. The study concluded that it is possible to contribute to the endowment of money in the development processes of all levels proven in the development equation, and that it is possible to adopt the developmental model approved in the scientific endowment because it relies on one of the theories such as Kaizen and Balanced scorecards in the organization of institutions.
أطروحة دكتوراه في العلوم الإسلامية تخصص فقه وأصول
Keywords: الوقف، الوقف النقدي، البحث العلمي، الوقف العلمي; endowment, cash endowment, scientific research, scientific endowment, Money.